The (political) economics of bilateral investment treaties: The unique trajectory of Brazil - Christian Bellak; Markus Leibrecht (Economies, 2024)
Brazil, after signing several traditional Bilateral Investment Treaties without ratifying them, recently shifted towards a different type of bilateral investment agreement, i.e., Investment Cooperation and Facilitation Agreements. Two claims have been made in the literature regarding the transition from traditional Bilateral Investment Treaties to Investment Cooperation and Facilitation Agreements-Claim #1: The non-ratification of the traditional BITs has not harmed Foreign Direct Investment into Brazil, a claim which puts into question the purpose of Bilateral Investment Treaties. Claim #2: While Investment Cooperation and Facilitation Agreements avoid some of the problems of traditional Bilateral Investment Treaties, on balance they are less effective than traditional Bilateral Investment Treaties would have been. We examine the two claims from an empirical economic point of view. We build on the literature about Brazil's position vis-à-vis Bilateral Investment Treaties, which must be viewed by an amalgamation of (i) a historical legacy; (ii) domestic initiatives, and (iii) a particular U-turn in the political debate. Using empirical evidence on Foreign Direct Investment effects of Bilateral Investment Treaties, the following conclusions emerge: With regard to claim #1, empirical evidence in general as well as specific to Brazil suggests that Brazil has forgone Foreign Direct Investment by not ratifying traditional Bilateral Investment Treaties. Concerning claim #2, while Investment Cooperation and Facilitation Agreements include alternative dispute settlement mechanisms, which aim at a better compliance of states with the Investment Cooperation and Facilitation Agreements' rules, rather than the compensation of foreign investors, the lower stringency of the State-State dispute settlement mechanism compared to Investor-State dispute settlement mechanism makes Investment Cooperation and Facilitation Agreements less effective. Yet, this weakening effect must be weighed against the effects on Foreign Direct Investment from innovative clauses in Investment Cooperation and Facilitation Agreements, which are absent in many traditional Bilateral Investment Treaties.
Keywords: 330; Brazil; foreign direct investment; hold-up; investment treaties